2019
DOI: 10.1016/j.numecd.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional eating in type 2 diabetes mellitus: A multicenter Italian study of socio-demographic and clinical associations

Abstract: Background and aims: Dysfunctional eating might impact on the management and metabolic control of type 2 diabetes (T2DM), modifying adherence to healthy diet and food choices. Methods and results: In a multicenter study, we assessed the prevalence of dysfunctional eating in 895 adult outpatients with T2DM (51% males, median age 67, median BMI 30.3 kg/m 2). Sociodemographic and clinical characteristics were recorded; dysfunctional eating was tested by validated questionnaires (Eating Attitude Test-EAT-26, Binge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 34 publications
1
20
1
2
Order By: Relevance
“…Prevalence rates in patients with T2DM have ranged widely from a point prevalence of 1.4 to 25%. 7,8,19,23,24 Some studies however, like that by Kenardy et al, 22 noted an association between T2DM and some degree of binge eating, but not BED itself. These conflicting results may be due to differences in exclusionary criteria, sample characteristics, and the setting in which participants were recruited.…”
Section: Prevalencementioning
confidence: 97%
See 2 more Smart Citations
“…Prevalence rates in patients with T2DM have ranged widely from a point prevalence of 1.4 to 25%. 7,8,19,23,24 Some studies however, like that by Kenardy et al, 22 noted an association between T2DM and some degree of binge eating, but not BED itself. These conflicting results may be due to differences in exclusionary criteria, sample characteristics, and the setting in which participants were recruited.…”
Section: Prevalencementioning
confidence: 97%
“…Many, 7,8,[18][19][20] but not all, 21,22 studies have reported a greater prevalence of BED in patients with T2DM than those without T2DM. Prevalence rates in patients with T2DM have ranged widely from a point prevalence of 1.4 to 25%.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…42.7 % of the participant T2DM individuals demonstrated impaired eating behaviors. The rate of these eating behaviors was reported to be 40 % in the systematic review done by Garcia-Mayor et al [6], 20 % in the study of Papelbaum et al [7], 19.6 % in the study of Petroni et al [11], 12.2 % in the study of Nicolau et al [8] and 39.3 % in the study of Yılmaz and Çetinkalp [9]. Such factors as age, gender, metabolic status influence eating attitudes.…”
Section: Discussionmentioning
confidence: 96%
“…Data for the current study were collected by means of Eating Attitudes Test, Diabetes Quality of Life Measure, and a Patient Information Form developed by the researchers following a comprehensive review of the literature [7,[10][11][12][13]. After the questionnaire form was prepared, a preliminary interview was held with 5 patients and necessary corrections were made and the investigation started.…”
Section: Data Collectionmentioning
confidence: 99%